Corak Pemikiran Dakwah Mohammad Natsir - Sugianto (Mau'idhoh Hasanah, 2019)
This written discussed thought of Mohammad Natsir. The method applied to discusse thought of Mohammad Natsir was literature review through books or article which concern object researched or document supporter, such as, journal and article. This written was used text study with used perspective hermeneutic to interpretation disgn of his thought. The result of reseach was that through dakwah of Muhammad Natsir was religious-politic.